THE EFFECT OF HUMAN RESOURCE QUALITY AND UTILIZATION OF INFORMATION TECHNOLOGY ON THE QUALITY OF FINANCIAL ACCOUNTABILITY REPORT WITH INTERNAL CONTROL AS AN INTERVENING VARIABLE (Empirical Study of BOS SMA / SMK Cilegon) - Amrullah, Ihsan (Pascasarjana Universitas Sultan Ageng Tirtayas, 2019)
This study aims to examine the effect of the quality of human resources and the use of information technology on the quality of the financial accountability report with internal control as an intervening variable in SMA/ SMK throughout Cilegon City. The population in this study was all educational units with an analysis unit of all the SMA/SMK Cilegon. The sampling in this study are 47 principal and 47 treasurer. The data in this study were analyzed using the Path Analysis using SPSS Ver.22. The results indicate that the quality of human resources doesn’t affected the quality of financial accountability reports, the use of information technology affected the quality of financial accountability reports, the human resources quality doesn’t affected internal control, the use of information technology affected internal control ,Internal control has significant effect the quality of financial accountability reports. In addition, the human resources quality indirectly affected the quality of financial accountability reports through internal control, indirect use of information technology affected the quality of financial accountability reports through internal control. Keywords : Quality of human resources, utilization of information technology, internal control and quality of financial accountability reports.